Teknik termodifikasi untuk memprediksi jarak privasi dan gangguan pada ruang kantor terbuka - Sentagi Sesotya Utami; Joko Sarwono; Zulfi Aulia Rachman (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Open-plan offices have become widely adopted in various industries as a workplace environment. However, this office layout type suffers from speech privacy, which can be represented by the acoustic parameter known as the Speech Transmission Index (STI). ISO 3382-3:2012 provides guidelines for calculating the acoustic parameters of a room tailored explicitly for open-plan offices. However, the existing method in ISO 3382-3:2012 requires a parallel layout of workstations to determine the STI value, which is hardly found in modern office settings. This study presents a technique to predict the ideal values of rP and rD, based on the relationship between %Alcons and the Speech Transmission Index (STI) for a specific workstation, using linear regression and in-situ measurements. The analysis of acoustic conditions in an open-plan office reveals that modified techniques can predict the acoustic quality in a modern office layout. The D2, S values indicate good acoustic quality, but the Lp, A, S,4m values do not meet the required standard. Using %Alcons equations, the study shows how to predict distraction distances and categorize workstations as 'Distracted' or 'Not distracted'. The results indicate only a small percentage of workstations allow for private communication.